2020
DOI: 10.3390/ijerph17176363
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress, Physiological Response, and Heat-Related Symptoms among Thai Sugarcane Workers

Abstract: Prolonged or intense exposure to heat can lead to a range of health effects. This study investigated heat exposure and heat-related symptoms which sugarcane workers (90 sugarcane cutters and 93 factory workers) experienced during a harvesting season in Thailand. During the hottest month of harvesting season, wet bulb globe temperature was collected in the work environment, and workloads observed, to assess heat stress. Urine samples for dehydration test, blood pressure, heart rate, and body temperature were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
1
16
1
1
Order By: Relevance
“…This indicates that the urine was normal and slightly acidic. This is in accord with findings from studies of Thai sugarcane workers, who tended to have acidic urine (pH 5-6) [31]. We also tested whether age and work experience were associated with urine pH level and specific gravity.…”
Section: Discussionsupporting
confidence: 82%
“…This indicates that the urine was normal and slightly acidic. This is in accord with findings from studies of Thai sugarcane workers, who tended to have acidic urine (pH 5-6) [31]. We also tested whether age and work experience were associated with urine pH level and specific gravity.…”
Section: Discussionsupporting
confidence: 82%
“…A study on sugarcane cutters with an increased risk of heat stress found a significant increase in heart rate, temperature, and blood pressure (SBP) occurred across the work shift [32]. However, another study found a significant increase in heat rate, but a decrease of SBP and DBP across 4 h shifts in sugarcane cutter in El Salvador [33].…”
Section: Discussionmentioning
confidence: 99%
“…Most of those affected were farmers because these workers are exposed to heat in full sunlight and have a heavy workload throughout their working lifetime 14 ) . Likewise, a previous study among Thai sugarcane cutters demonstrated that working in the extreme heat with a heavy workload is associated with heat-related illness symptoms 15 ) .…”
Section: Introductionmentioning
confidence: 89%
“…All participants were asked whether they had experienced each symptom during the summer at work; responses were “never”, “sometimes”, or “regularly” (at least once per week). For data analysis, “sometimes” and “regularly” were grouped into one variable, denoted “ever” 15 ) . The third part of the questionnaire addressed occupational factors, including heat exposure duration per day, work clothing ensembles, and fluid intake per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation